Particle granulator for special engineering plastic production - XU SHOUXIN; ZHANG XINGZI (2024)
The invention discloses a granulator for special engineering plastic production, and relates to the technical field of granulators. The device comprises a frame body; the extrusion injection molding mechanism comprises an injection molding barrel fixedly connected to the frame body, a feeding hopper is constructed on the upper side of one end of the injection molding barrel, a heating box located under the feeding hopper is installed between the frame body and the injection molding barrel, an extrusion molding net is constructed at the other end of the injection molding barrel, and a screw rod is rotationally installed in the injection molding barrel; and the crushing and feeding assembly comprises a mounting frame fixedly connected to the frame body. According to the device, the crushing and feeding assembly connected with the extrusion injection molding mechanism is mounted on the frame body, so that recycled large-block plastic can be extruded and crushed through a crushing roller in the crushing and feedi